CN107518440A - A kind of antibacterial non-slip socks that can increase the height of socks - Google Patents
A kind of antibacterial non-slip socks that can increase the height of socks Download PDFInfo
- Publication number
- CN107518440A CN107518440A CN201711032334.7A CN201711032334A CN107518440A CN 107518440 A CN107518440 A CN 107518440A CN 201711032334 A CN201711032334 A CN 201711032334A CN 107518440 A CN107518440 A CN 107518440A
- Authority
- CN
- China
- Prior art keywords
- parts
- sock
- socks
- antibacterial
- stirred
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Granted
Links
Classifications
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B11/00—Hosiery; Panti-hose
- A41B11/008—Hosiery with an anti-slip coating
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B11/00—Hosiery; Panti-hose
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B17/00—Selection of special materials for underwear
-
- A—HUMAN NECESSITIES
- A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
- A61H—PHYSICAL THERAPY APPARATUS, e.g. DEVICES FOR LOCATING OR STIMULATING REFLEX POINTS IN THE BODY; ARTIFICIAL RESPIRATION; MASSAGE; BATHING DEVICES FOR SPECIAL THERAPEUTIC OR HYGIENIC PURPOSES OR SPECIFIC PARTS OF THE BODY
- A61H15/00—Massage by means of rollers, balls, e.g. inflatable, chains, or roller chains
-
- A—HUMAN NECESSITIES
- A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
- A61H—PHYSICAL THERAPY APPARATUS, e.g. DEVICES FOR LOCATING OR STIMULATING REFLEX POINTS IN THE BODY; ARTIFICIAL RESPIRATION; MASSAGE; BATHING DEVICES FOR SPECIAL THERAPEUTIC OR HYGIENIC PURPOSES OR SPECIFIC PARTS OF THE BODY
- A61H39/00—Devices for locating or stimulating specific reflex points of the body for physical therapy, e.g. acupuncture
- A61H39/04—Devices for pressing such points, e.g. Shiatsu or Acupressure
-
- A—HUMAN NECESSITIES
- A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
- A61H—PHYSICAL THERAPY APPARATUS, e.g. DEVICES FOR LOCATING OR STIMULATING REFLEX POINTS IN THE BODY; ARTIFICIAL RESPIRATION; MASSAGE; BATHING DEVICES FOR SPECIAL THERAPEUTIC OR HYGIENIC PURPOSES OR SPECIFIC PARTS OF THE BODY
- A61H7/00—Devices for suction-kneading massage; Devices for massaging the skin by rubbing or brushing not otherwise provided for
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B2300/00—Details of shirts, underwear, baby linen or handkerchiefs not provided for in other groups of this subclass
- A41B2300/30—Closures
- A41B2300/322—Closures using slide fasteners
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B2400/00—Functions or special features of shirts, underwear, baby linen or handkerchiefs not provided for in other groups of this subclass
- A41B2400/32—Therapeutic use
- A41B2400/322—Massage
-
- A—HUMAN NECESSITIES
- A41—WEARING APPAREL
- A41B—SHIRTS; UNDERWEAR; BABY LINEN; HANDKERCHIEFS
- A41B2400/00—Functions or special features of shirts, underwear, baby linen or handkerchiefs not provided for in other groups of this subclass
- A41B2400/34—Functions or special features of shirts, underwear, baby linen or handkerchiefs not provided for in other groups of this subclass antimicrobial or antibacterial
-
- A—HUMAN NECESSITIES
- A61—MEDICAL OR VETERINARY SCIENCE; HYGIENE
- A61H—PHYSICAL THERAPY APPARATUS, e.g. DEVICES FOR LOCATING OR STIMULATING REFLEX POINTS IN THE BODY; ARTIFICIAL RESPIRATION; MASSAGE; BATHING DEVICES FOR SPECIAL THERAPEUTIC OR HYGIENIC PURPOSES OR SPECIFIC PARTS OF THE BODY
- A61H2205/00—Devices for specific parts of the body
- A61H2205/12—Feet
- A61H2205/125—Foot reflex zones
Landscapes
- Health & Medical Sciences (AREA)
- Rehabilitation Therapy (AREA)
- Engineering & Computer Science (AREA)
- General Health & Medical Sciences (AREA)
- Physical Education & Sports Medicine (AREA)
- Pain & Pain Management (AREA)
- Life Sciences & Earth Sciences (AREA)
- Animal Behavior & Ethology (AREA)
- Epidemiology (AREA)
- Public Health (AREA)
- Veterinary Medicine (AREA)
- Textile Engineering (AREA)
- Dermatology (AREA)
- Chemical & Material Sciences (AREA)
- Materials Engineering (AREA)
- Compositions Of Macromolecular Compounds (AREA)
Abstract
Description
技术领域technical field
本发明涉及一种可增高袜筒的抗菌防滑袜子。The invention relates to an antibacterial anti-skid sock which can increase the height of the sock tube.
背景技术Background technique
袜子是人们生活中不可缺少的生活用品,无论是行走、运动还是漫步时都会使用到,由于部分袜子透气性差的关系,脚经常处于潮湿、不透气的微环境,容易滋生细菌,产生脚气等危害脚部,而且一般袜子基本都是针织而成,摩擦系数小而且抓地力不高,防滑效果差,并且一袜子不能随意的加高,在一些特殊的场合,低筒袜无法加高。Socks are an indispensable daily necessities in people's lives. They are used whether they are walking, exercising or strolling. Due to the poor air permeability of some socks, the feet are often in a humid and airtight microenvironment, which is easy to breed bacteria and cause beriberi and other hazards. Feet, and general socks are basically knitted, with small friction coefficient and low grip, poor anti-skid effect, and a sock cannot be heightened at will. In some special occasions, low socks cannot be heightened.
发明内容Contents of the invention
针对上述存在的问题,本发明提供一种可增高袜筒的抗菌防滑袜子,能够自主加高袜筒,具有防滑以及抗菌性能。In view of the above existing problems, the present invention provides an antibacterial and non-slip sock that can increase the height of the sock tube, which can increase the height of the sock tube independently, and has anti-slip and antibacterial properties.
为了实现上述目的,本发明提供的技术方案是:一种可增高袜筒的抗菌防滑袜子,它包括袜筒和袜本体,所述的袜本体底部具有若干个间隔排列的防滑条;In order to achieve the above object, the technical solution provided by the present invention is: an antibacterial anti-skid sock that can increase the height of the sock, which includes a sock and a sock body, and the bottom of the sock body has several anti-skid strips arranged at intervals;
所述的袜筒上还具有可拆卸的加高套,所述的加高套与袜筒通过拉链机构固定连接,The sock tube also has a detachable heightening sleeve, and the heightening sleeve and the sock tube are fixedly connected by a zipper mechanism,
所述的袜子本体的里层都粘附有纳米抗菌材料。The inner layers of the socks body are all adhered with nano antibacterial materials.
所述的相邻的防滑条之间还设有按摩凸起,所述的按摩凸起黏贴在袜子本体表面。Massage protrusions are also provided between the adjacent anti-slip strips, and the massage protrusions are stuck on the surface of the sock body.
所述的纳米抗菌材料以聚乙烯、Cu-MOF-Al2O3纳米材料、甲酸乙酯、聚乳酸、碳酸钠、月桂基甜菜碱、三聚磷酸钠和二甲苯磺酸钠为主要原料制备。The nano antibacterial material is prepared from polyethylene, Cu-MOF - Al2O3 nanomaterials, ethyl formate, polylactic acid, sodium carbonate, lauryl betaine, sodium tripolyphosphate and sodium xylene sulfonate as main raw materials .
本发明它包括袜筒和袜本体,所述的袜本体底部具有若干个间隔排列的防滑条,具有非常好的防滑效果,袜筒上还具有可拆卸的加高套,所述的加高套与袜筒通过拉链机构固定连接,能够方便的加高或者降低袜筒高度,适用环境需要,所述的袜子的里层都粘附有纳米抗菌材料,采用特殊的纳米抗菌材料,其抗菌效果好,相邻的防滑条之间还设有按摩凸起,所述的按摩凸起黏贴在袜子本体表面,对于脚底具有按摩疏筋功效。The present invention includes a sock tube and a sock body. The bottom of the sock body has several anti-slip strips arranged at intervals, which has a very good anti-skid effect. The sock tube also has a detachable heightening sleeve. The heightening sleeve It is fixedly connected with the sock tube through a zipper mechanism, which can easily increase or decrease the height of the sock tube, and is suitable for the environment. The inner layer of the socks is adhered with nano-antibacterial materials. The special nano-antibacterial material is used, and its antibacterial effect is good. There are also massage protrusions between the adjacent anti-slip strips, and the massage protrusions are pasted on the surface of the sock body, and have the effect of massaging and loosening tendons on the soles of the feet.
附图说明Description of drawings
图1为本发明结构示意图;Fig. 1 is a structural representation of the present invention;
图2为袜本体底部示意图;Fig. 2 is a schematic diagram of the bottom of the sock body;
图中:1、袜本体、2、袜筒、3、加高套、4、拉链机构,5、防滑条,6、按摩凸起。In the figure: 1. Sock body, 2. Sock tube, 3. Heightening cover, 4. Zipper mechanism, 5. Anti-slip strip, 6. Massage protrusion.
具体实施方式detailed description
下面将结合本发明实施例中的附图,对本发明实施例中的技术方案进行清楚、完整地描述,显然,所描述的实施例仅仅是本发明一部分实施例,而不是全部的实施例。基于本发明中的实施例,本领域普通技术人员在没有做出创造性劳动前提下所获得的所有其他实施例,都属于本发明保护的范围。The following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only some, not all, embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without making creative efforts belong to the protection scope of the present invention.
请参阅图1和2,一种可增高袜筒的抗菌防滑袜子,它包括袜筒2和袜本体1,所述的袜本体底部具有若干个间隔排列的防滑条5;Please refer to Figures 1 and 2, a kind of antibacterial non-slip socks that can increase the height of the sock, it includes a sock 2 and a sock body 1, and the bottom of the sock body has several anti-skid strips 5 arranged at intervals;
所述的袜筒上还具有可拆卸的加高套3,所述的加高套与袜筒通过拉链机构4固定连接,There is also a detachable heightening cover 3 on the sock tube, and the heightening cover and the sock tube are fixedly connected by a zipper mechanism 4,
所述的袜子本体的里层都粘附有纳米抗菌材料。The inner layers of the socks body are all adhered with nano antibacterial materials.
所述的相邻的防滑条之间还设有按摩凸起6,所述的按摩凸起黏贴在袜子本体表面。Massage protrusions 6 are also provided between the adjacent anti-slip strips, and the massage protrusions are stuck on the surface of the sock body.
本发明它包括袜筒和袜本体,所述的袜本体底部具有若干个间隔排列的防滑条,具有非常好的防滑效果,袜筒上还具有可拆卸的加高套,所述的加高套与袜筒通过拉链机构固定连接,能够方便的加高或者降低袜筒高度,适用环境需要,所述的袜子的里层都粘附有纳米抗菌材料,采用特殊的纳米抗菌材料,其抗菌效果好,相邻的防滑条之间还设有按摩凸起,所述的按摩凸起黏贴在袜子本体表面,对于脚底具有按摩疏筋功效。The present invention includes a sock tube and a sock body. The bottom of the sock body has several anti-slip strips arranged at intervals, which has a very good anti-skid effect. The sock tube also has a detachable heightening sleeve. The heightening sleeve It is fixedly connected with the sock tube through a zipper mechanism, which can easily increase or decrease the height of the sock tube, and is suitable for the environment. The inner layer of the socks is adhered with nano-antibacterial materials. The special nano-antibacterial material is used, and its antibacterial effect is good. There are also massage protrusions between the adjacent anti-slip strips, and the massage protrusions are pasted on the surface of the sock body, and have the effect of massaging and loosening tendons on the soles of the feet.
所述的纳米抗菌材料以聚乙烯、Cu-MOF-Al2O3纳米材料、甲酸乙酯、聚乳酸、碳酸钠、月桂基甜菜碱、三聚磷酸钠和二甲苯磺酸钠为主要原料制备。The nano antibacterial material is prepared from polyethylene, Cu-MOF - Al2O3 nanomaterials, ethyl formate, polylactic acid, sodium carbonate, lauryl betaine, sodium tripolyphosphate and sodium xylene sulfonate as main raw materials .
本发明袜子的里层都粘附有纳米抗菌材料,该材料利用多孔氧化铝与Cu-MOF原位交联形成具有网络结构的复合材料基体,且在基体材料形成过程中,基体材料中的铜离子可均匀分散在基体交联的网络结构中,提高材料的抗菌稳定性;MOF有机配体构建双层结构平台,将聚乙烯上隐藏在一个抗生物污染的“干净”表面下,在干态条件下,最外层的分子刷表面失水坍塌,使内部的抗菌聚合物以接触杀菌方式杀死细菌,对大肠杆菌和葡萄球菌均具有较好的抗菌效果。The inner layers of the socks of the present invention are all adhered with nano-antibacterial materials, which utilize porous alumina and Cu-MOF in-situ cross-linking to form a composite material matrix with a network structure, and during the formation of the matrix material, the copper in the matrix material The ions can be evenly dispersed in the cross-linked network structure of the matrix to improve the antibacterial stability of the material; the MOF organic ligand builds a double-layer structure platform, hiding the polyethylene under a "clean" surface that is resistant to biofouling. Under certain conditions, the surface of the outermost molecular brush loses water and collapses, so that the internal antibacterial polymer kills bacteria by contact sterilization, and has a good antibacterial effect on both Escherichia coli and Staphylococcus.
更为具体的制备方法如下:A more specific preparation method is as follows:
抗菌材料的制备方法,该方法包括以下步骤:A method for preparing an antibacterial material, the method comprising the following steps:
步骤1、将65份聚乙烯、13份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 65 parts of polyethylene, 13 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
步骤2、将1.5份抗氧化剂BHT和1.3份助抗氧剂DLTP加入到步骤1得到的初产物中,在温度为80℃条件下搅拌混合均匀,搅拌速度为200转/分钟,搅拌时间为30分钟;Step 2. Add 1.5 parts of antioxidant BHT and 1.3 parts of co-antioxidant DLTP to the primary product obtained in step 1, stir and mix evenly at a temperature of 80°C, the stirring speed is 200 rpm, and the stirring time is 30 minute;
步骤3、将步骤2得到的混合物于双螺杆挤出机中挤出,挤出条件为双螺杆挤出机筒后段温度分三段控制,分别控制在180℃、185℃和190℃,料筒前段温度分三段控制,分别控制在195℃、200℃和210℃,机头温度分两段控制,分别控制在230℃和236℃,最终得到医用纳米抗菌复合材料。Step 3. Extrude the mixture obtained in step 2 in a twin-screw extruder. The extrusion condition is that the temperature of the rear section of the twin-screw extruder barrel is controlled in three sections, respectively controlled at 180°C, 185°C and 190°C. The temperature of the front section of the cylinder is controlled in three stages, respectively controlled at 195°C, 200°C and 210°C, and the temperature of the head is controlled in two stages, respectively controlled at 230°C and 236°C, and finally the medical nano-antibacterial composite material is obtained.
所述的Cu-MOF-Al2O3纳米材料制备方法如下:The preparation method of the Cu-MOF-Al 2 O 3 nanometer material is as follows:
步骤1、将10份氧化铝粉、0.3份聚丙烯酸钠、19.4份茨烯、2.9份叔丁醇和0.5份氧化钇混合放入烧瓶中,在75℃下均匀搅拌,得到浆料;Step 1. Mix 10 parts of alumina powder, 0.3 parts of sodium polyacrylate, 19.4 parts of tertene, 2.9 parts of tert-butanol and 0.5 parts of yttrium oxide into a flask, and stir evenly at 75°C to obtain a slurry;
步骤2、将浆料倒入模具中,在-16℃下放置,得到成型为柱状的氧化铝多孔颗粒塑坯;Step 2. Pour the slurry into a mold and place it at -16°C to obtain a columnar alumina porous particle preform;
步骤3、将氧化铝多孔颗粒塑坯先在-16℃下放置12h,然后将其放入冷冻干燥机中在-60℃条件下干燥6h,最后以4℃/min的速度升温进行高温烧结,升温至1000℃,保温3h,冷却后得到多孔氧化铝基体;Step 3. Place the preform of porous alumina particles at -16°C for 12 hours, then put it into a freeze dryer and dry it at -60°C for 6 hours, and finally heat up at a rate of 4°C/min for high-temperature sintering. Raise the temperature to 1000°C, keep it warm for 3 hours, and obtain a porous alumina matrix after cooling;
步骤4、取4.2份均苯三甲酸,加入到25份质量分数95%的乙醇溶液中,作为配体溶液待用;Step 4, get 4.2 parts of trimesic acid, join in 25 parts of ethanol solution of mass fraction 95%, stand-by as ligand solution;
步骤5、将制备好的多孔氧化铝基体在足量的上述配体溶液中浸渍5h;Step 5, immersing the prepared porous alumina matrix in a sufficient amount of the above-mentioned ligand solution for 5 hours;
步骤6、将上述浸渍好的多孔氧化铝基体过滤后放入放入足量浓度为0.5 mol/L的硝酸铜溶液中,于80℃油浴中并在冷凝回流条件下反应22h,过滤,干燥(干燥的温度为100℃),干燥的时间为12h)后得到Cu-MOF-Al2O3纳米材料。Step 6. After filtering the impregnated porous alumina matrix, put it into a copper nitrate solution with a sufficient concentration of 0.5 mol/L, react in an oil bath at 80°C for 22 hours under condensing and reflux conditions, filter, and dry (the drying temperature is 100°C), and the drying time is 12h) to obtain Cu-MOF-Al 2 O 3 nanomaterials.
实施例2Example 2
步骤1、将50份聚乙烯、16份Cu-MOF-Al2O3纳米材料、4份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 50 parts of polyethylene, 16 parts of Cu-MOF-Al 2 O 3 nanomaterials, 4 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例3Example 3
步骤1、步骤1、将45份聚乙烯、23份Cu-MOF-Al2O3纳米材料、6份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1, step 1, adding 45 parts of polyethylene, 23 parts of Cu-MOF-Al 2 O 3 nanomaterials, 6 parts of ethyl formate and 5 parts of polylactic acid into the reactor, adding 1 part of sodium carbonate, 5 parts of lauryl Base betaine, 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm minutes, the mixing time was 30 minutes, then the temperature was raised to 80°C under a vacuum of 0.01MPa, stirred for 20 minutes, and then heated to 130°C, stirred and reacted for 30 minutes to obtain the initial product;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例4Example 4
步骤1、将38份聚乙烯、19份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 38 parts of polyethylene, 19 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例5Example 5
步骤1、将17份聚乙烯、3份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 17 parts of polyethylene, 3 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例6Example 6
步骤1、将65份聚乙烯、13份Cu-MOF-Al2O3纳米材料、5份甲酸乙酯和1份聚乳酸加入到反应釜中,将4份碳酸钠、3份月桂基甜菜碱、6份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 65 parts of polyethylene, 13 parts of Cu-MOF-Al 2 O 3 nanomaterials, 5 parts of ethyl formate and 1 part of polylactic acid into the reaction kettle, add 4 parts of sodium carbonate, 3 parts of lauryl betaine , 6 parts of sodium tripolyphosphate and 0.8 parts of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly under the condition of 50 ° C, and the stirring speed of stirring and mixing was 150 rpm, and the mixing The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例7Example 7
步骤1、将34份聚乙烯、23份Cu-MOF-Al2O3纳米材料、8份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 34 parts of polyethylene, 23 parts of Cu-MOF-Al 2 O 3 nanomaterials, 8 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例8Example 8
步骤1、将34份聚乙烯、17份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、6份三聚磷酸钠和4份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 34 parts of polyethylene, 17 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 5 parts of lauryl betaine , 6 parts of sodium tripolyphosphate and 4 parts of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly under the condition of 50 ° C, and the stirring speed of stirring and mixing was 150 revolutions per minute, mixing The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例9Example 9
步骤1、将65份聚乙烯、23份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将3份碳酸钠、1份月桂基甜菜碱、1份三聚磷酸钠和2.1份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 65 parts of polyethylene, 23 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 3 parts of sodium carbonate, 1 part of lauryl betaine , 1 part of sodium tripolyphosphate and 2.1 parts of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly under the condition of 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例10Example 10
步骤1、将75份聚乙烯、37份Cu-MOF-Al2O3纳米材料、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、8份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 75 parts of polyethylene, 37 parts of Cu-MOF-Al 2 O 3 nanomaterials, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, 8 parts of lauryl betaine , 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate were dissolved in 30 parts of water, then added to the reaction kettle, stirred and mixed evenly at 50 ° C, and the stirring speed of stirring and mixing was 150 rpm. The time is 30 minutes, and then the temperature is raised to 80°C under a vacuum degree of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
实施例11Example 11
步骤1、将65份聚乙烯、13份Cu-MOF-Al2O3纳米材料、8份改性碳纤维、3份甲酸乙酯和5份聚乳酸加入到反应釜中,将1份碳酸钠、5份月桂基甜菜碱、1份三聚磷酸钠和0.8份二甲苯磺酸钠溶于30份水中,然后加入反应釜中,在50℃条件下搅拌混合均匀,其中搅拌混合均匀的搅拌速度为150转/分钟,混合时间为30分钟,然后在真空度为0.01MPa下升温至80℃,搅拌20分钟,再升温至130℃,搅拌反应30分钟,得到初产物;Step 1. Add 65 parts of polyethylene, 13 parts of Cu-MOF-Al 2 O 3 nanomaterials, 8 parts of modified carbon fiber, 3 parts of ethyl formate and 5 parts of polylactic acid into the reaction kettle, add 1 part of sodium carbonate, Dissolve 5 parts of lauryl betaine, 1 part of sodium tripolyphosphate and 0.8 part of sodium xylene sulfonate in 30 parts of water, then add them into the reaction kettle, stir and mix evenly at 50°C, and the stirring speed for mixing evenly is 150 revolutions per minute, the mixing time is 30 minutes, then the temperature is raised to 80°C under a vacuum of 0.01MPa, stirred for 20 minutes, then heated to 130°C, stirred and reacted for 30 minutes, and the initial product is obtained;
其余制备和实施例1相同。All the other preparations are the same as in Example 1.
所述的改性碳纤维制备方法如下:Described modified carbon fiber preparation method is as follows:
将碳纤维置于丙酮溶液中浸泡12h,过滤,去离子水洗涤3次,120℃鼓风干燥机中干燥4h,用60%硝酸回流氧化碳纤维7h,过滤,去离子水洗涤PH=6,于120℃鼓风干燥机中干燥至恒重;将硝酸氧化的碳纤维置于聚乙烯吡咯烷酮、十二烷基硫酸钠及相当于其总重量份的12倍的去离子水配置的溶液中,超声50min,60℃干燥,得到表面改性的碳纤维。Soak the carbon fibers in acetone solution for 12 hours, filter, wash with deionized water for 3 times, dry in a blast dryer at 120°C for 4 hours, reflux with 60% nitric acid to oxidize the carbon fibers for 7 hours, filter, wash with deionized water at pH=6, at 120 ℃ in a blower dryer to constant weight; place the carbon fiber oxidized by nitric acid in a solution prepared by polyvinylpyrrolidone, sodium lauryl sulfate and deionized water equivalent to 12 times the total weight of the solution, ultrasonic for 50min, Dry at 60°C to obtain surface-modified carbon fibers.
对照例1Comparative example 1
与实施例1不同点在于:抗菌纳米材料的步骤2中,将2份抗氧化剂BHT和0.3份助抗氧剂DLTP加入到步骤1得到的初产物中,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 2 of antibacterial nanomaterials, 2 parts of antioxidant BHT and 0.3 part of co-antioxidant DLTP are added to the primary product obtained in step 1, and the rest of the steps are exactly the same as in Example 1.
对照例2Comparative example 2
与实施例1不同点在于:抗菌纳米材料的步骤2中,将0.3份抗氧化剂BHT和2份助抗氧剂DLTP加入到步骤1得到的初产物中,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 2 of antibacterial nanomaterials, 0.3 parts of antioxidant BHT and 2 parts of co-antioxidant DLTP are added to the primary product obtained in step 1, and the rest of the steps are exactly the same as in Example 1.
对照例3Comparative example 3
与实施例1不同点在于:抗菌纳米材料的步骤3中,双螺杆挤出机筒后段温度分三段控制,分别控制在150℃、155℃和160℃,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of antibacterial nanomaterials, the temperature of the rear section of the twin-screw extruder barrel is controlled in three stages, respectively controlled at 150°C, 155°C and 160°C, and the rest of the steps are exactly the same as in Example 1 .
对照例4Comparative example 4
与实施例1不同点在于:抗菌纳米材料的步骤3中,双螺杆挤出机筒后段温度分三段控制,分别控制在190℃、195℃和200℃,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of antibacterial nanomaterials, the temperature of the rear section of the twin-screw extruder barrel is controlled in three stages, respectively controlled at 190°C, 195°C and 200°C, and the rest of the steps are exactly the same as in Example 1 .
对照例5Comparative example 5
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤1中,将8份氧化铝粉、3份聚丙烯酸钠、14份茨烯、2.9份叔丁醇和0.5份氧化钇混合放入烧瓶中,在75℃下均匀搅拌,得到浆料,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 1 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, 8 parts of alumina powder, 3 parts of sodium polyacrylate, 14 parts of zene, 2.9 parts of tert-butanol and 0.5 parts of oxidized Yttrium was mixed and put into a flask, stirred evenly at 75° C. to obtain a slurry, and the rest of the steps were exactly the same as in Example 1.
对照例6Comparative example 6
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤1中,将16份氧化铝粉、0.1份聚丙烯酸钠、6份茨烯、9份叔丁醇和3份氧化钇混合放入烧瓶中,在75℃下均匀搅拌,得到浆料,其余步骤与实施例1完全相同。The difference from Example 1 is that in Step 1 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, 16 parts of alumina powder, 0.1 part of sodium polyacrylate, 6 parts of zene, 9 parts of tert-butanol and 3 parts of oxidation Yttrium was mixed and put into a flask, stirred evenly at 75° C. to obtain a slurry, and the rest of the steps were exactly the same as in Example 1.
对照例7Comparative example 7
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤3中,放入冷冻干燥机中在-60℃条件下干燥6h,最后以15℃/min的速度升温进行高温烧结,升温至1000℃,保温3h,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, put it in a freeze dryer and dry it at -60°C for 6 hours, and finally heat up at a speed of 15°C/min for high temperature Sintering, heating up to 1000°C, keeping the temperature for 3 hours, and the rest of the steps are exactly the same as in Example 1.
对照例8Comparative example 8
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤3中,放入冷冻干燥机中在-60℃条件下干燥6h,最后以25℃/min的速度升温进行高温烧结,升温至1000℃,保温3h,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, put it into a freeze dryer and dry it at -60°C for 6 hours, and finally heat up at a speed of 25°C/min for high temperature Sintering, heating up to 1000°C, keeping the temperature for 3 hours, and the rest of the steps are exactly the same as in Example 1.
对照例9Comparative example 9
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤3中,将上述浸渍好的多孔氧化铝基体过滤后放入放入足量浓度为0.01mol/L的硝酸铜溶液中,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, the impregnated porous alumina substrate is filtered and then put into a sufficient amount of copper nitrate with a concentration of 0.01mol/L solution, all the other steps are exactly the same as in Example 1.
对照例10Comparative example 10
与实施例1不同点在于:Cu-MOF-Al2O3纳米材料制备的步骤3中,将上述浸渍好的多孔氧化铝基体过滤后放入放入足量浓度为1.0mol/L的硝酸铜溶液中,其余步骤与实施例1完全相同。The difference from Example 1 is that in step 3 of the preparation of Cu-MOF-Al 2 O 3 nanomaterials, the impregnated porous alumina matrix is filtered and put into a sufficient amount of copper nitrate with a concentration of 1.0 mol/L solution, all the other steps are exactly the same as in Example 1.
将以上实施例和对照例制备得到的抗菌材料进行性能测试,并测试第100天后其抗菌效果,结果如下;The antibacterial material that above embodiment and comparative example are prepared carry out performance test, and test its antibacterial effect after the 100th day, the result is as follows;
测试结果Test Results
实验结果表明本发明袜体内部的抗菌材料具有良好的抗菌效果,材料在标准测试条件下,细菌抑制率越低,说明抗菌效果好,反之,效果越差; 实施例1到实施例10,葡萄球菌和大肠杆菌抑制率均超过85%,分别改变抗菌材料中各个原料组成的配比,对材料的抗菌性能均有不同程度的影响,聚乙烯和Cu-MOF-Al2O3纳米材料质量配比为5:1,其他配料用量固定时,抗菌效果最好;值得注意的是实施例11加入改性碳纤维,抗菌效果明显提高,并且抗菌稳定性保持的非常的出色,说明改性碳纤维对Cu-MOF-Al2O3纳米隔离层结构的抗菌性能以及稳定性有更好的优化作用;对照例1至对照例2变化抗菌纳米材料抗氧化剂用量,抗菌效果明显下降,说明抗氧化剂及助氧化剂的用量对材料的抗菌性产生重要影响;对照例3和对照例4,改变三段控制温度的高低,合成的材料细菌抑制率依然很低,抗菌性能不佳;对照例5到对照例8改变Cu-MOF-Al2O3纳米材料的原料配比和升温速率,效果也不好,说明原料的组成和升温过程对Cu-MOF-Al2O3纳米材料得复合有重要影响;对照例9和例10改变浸渍过程中硝酸铜溶液的浓度,抗菌效果明显降低,说明硝酸铜过多过少都会对材料的细菌抑制率影响很大;因此使用抗菌材料在袜体内部具有良好的抗菌效果。Experimental results show that the antibacterial material inside the sock body of the present invention has good antibacterial effect, and the lower the bacterial inhibition rate of the material under standard test conditions, the better the antibacterial effect, otherwise, the worse the effect; Embodiment 1 to embodiment 10, grape The inhibition rates of coccus and Escherichia coli exceeded 85%. Changing the proportion of each raw material composition in the antibacterial material has different effects on the antibacterial performance of the material. The quality ratio of polyethylene and Cu-MOF-Al 2 O 3 nanomaterials The antibacterial effect is the best when the ratio of other ingredients is fixed at 5:1; it is worth noting that the modified carbon fiber is added in Example 11, the antibacterial effect is significantly improved, and the antibacterial stability is maintained very well, which shows that the modified carbon fiber has a good effect on Cu - The antibacterial properties and stability of the MOF-Al 2 O 3 nano-separation layer structure have a better optimization effect; the amount of anti-bacterial nanomaterial antioxidants is changed from control example 1 to control example 2, and the anti-bacterial effect is significantly reduced, indicating that antioxidants and pro-oxidants The amount of the material has an important impact on the antibacterial property of the material; for the control example 3 and the control example 4, change the height of the three-stage control temperature, the bacterial inhibition rate of the synthesized material is still very low, and the antibacterial performance is not good; the control example 5 to the control example 8 change The raw material ratio and heating rate of Cu-MOF-Al 2 O 3 nanomaterials are not effective, indicating that the composition of raw materials and the heating process have an important impact on the composite of Cu-MOF-Al 2 O 3 nanomaterials; Comparative Example 9 And example 10 changes the concentration of copper nitrate solution in the dipping process, the antibacterial effect is significantly reduced, indicating that too much or too little copper nitrate will have a great impact on the bacterial inhibition rate of the material; therefore, the use of antibacterial materials has a good antibacterial effect inside the socks.
Claims (4)
Priority Applications (2)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201811439295.7A CN109259335A (en) | 2017-10-29 | 2017-10-29 | A kind of antimicrobial socks |
| CN201711032334.7A CN107518440B (en) | 2017-10-29 | 2017-10-29 | A kind of antibacterial and non-slip socks that can increase the sock tube |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201711032334.7A CN107518440B (en) | 2017-10-29 | 2017-10-29 | A kind of antibacterial and non-slip socks that can increase the sock tube |
Related Child Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201811439295.7A Division CN109259335A (en) | 2017-10-29 | 2017-10-29 | A kind of antimicrobial socks |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN107518440A true CN107518440A (en) | 2017-12-29 |
| CN107518440B CN107518440B (en) | 2019-01-22 |
Family
ID=60685504
Family Applications (2)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201811439295.7A Pending CN109259335A (en) | 2017-10-29 | 2017-10-29 | A kind of antimicrobial socks |
| CN201711032334.7A Active CN107518440B (en) | 2017-10-29 | 2017-10-29 | A kind of antibacterial and non-slip socks that can increase the sock tube |
Family Applications Before (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201811439295.7A Pending CN109259335A (en) | 2017-10-29 | 2017-10-29 | A kind of antimicrobial socks |
Country Status (1)
| Country | Link |
|---|---|
| CN (2) | CN109259335A (en) |
Cited By (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN108451057A (en) * | 2018-05-25 | 2018-08-28 | 海宁市红枫针织有限责任公司 | A kind of silk stocking with buffering sole pressure |
| CN112516828A (en) * | 2020-11-28 | 2021-03-19 | 浙江千禧龙纤特种纤维股份有限公司 | Ultrahigh molecular polyethylene fiber varicose vein socks and production equipment thereof |
Citations (5)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN201919667U (en) * | 2010-12-22 | 2011-08-10 | 浙江百隆针织有限公司 | Pure cotton thickened female socks |
| CN105146775A (en) * | 2015-10-22 | 2015-12-16 | 海宁酷尔曼袜业有限公司 | Seamless toe sock |
| CN205456097U (en) * | 2016-04-01 | 2016-08-17 | 浙江希望之星针织有限公司 | Novel antiskid antibacterial socks |
| CN107173857A (en) * | 2017-07-18 | 2017-09-19 | 海宁市万事达袜业有限公司 | Anti-skidding nanometer deodorization socks are moved in a kind of damping |
| CN107594645A (en) * | 2017-10-29 | 2018-01-19 | 宁波科邦华诚技术转移服务有限公司 | A kind of antibacterial non-slip socks |
Family Cites Families (6)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN1115357C (en) * | 1999-11-02 | 2003-07-23 | 海尔科化工程塑料国家工程研究中心有限公司 | Resin composition containing antibacterial mildew inhibitor and its preparing process |
| CN201767047U (en) * | 2010-09-17 | 2011-03-23 | 海宁耐尔袜业有限公司 | Sock |
| CN202588284U (en) * | 2012-05-09 | 2012-12-12 | 宁波市鄞州民丰精纺织有限公司 | Sock |
| CN205337630U (en) * | 2016-01-22 | 2016-06-29 | 苏秀丽 | Novel silver fibre socks |
| CN205682452U (en) * | 2016-03-30 | 2016-11-16 | 武汉鑫大宸科技有限公司 | Nano-antibacterial socks |
| CN106937763A (en) * | 2017-05-21 | 2017-07-11 | 盐城巧丽袜业有限公司 | A kind of multi-functional short legging |
-
2017
- 2017-10-29 CN CN201811439295.7A patent/CN109259335A/en active Pending
- 2017-10-29 CN CN201711032334.7A patent/CN107518440B/en active Active
Patent Citations (5)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN201919667U (en) * | 2010-12-22 | 2011-08-10 | 浙江百隆针织有限公司 | Pure cotton thickened female socks |
| CN105146775A (en) * | 2015-10-22 | 2015-12-16 | 海宁酷尔曼袜业有限公司 | Seamless toe sock |
| CN205456097U (en) * | 2016-04-01 | 2016-08-17 | 浙江希望之星针织有限公司 | Novel antiskid antibacterial socks |
| CN107173857A (en) * | 2017-07-18 | 2017-09-19 | 海宁市万事达袜业有限公司 | Anti-skidding nanometer deodorization socks are moved in a kind of damping |
| CN107594645A (en) * | 2017-10-29 | 2018-01-19 | 宁波科邦华诚技术转移服务有限公司 | A kind of antibacterial non-slip socks |
Cited By (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN108451057A (en) * | 2018-05-25 | 2018-08-28 | 海宁市红枫针织有限责任公司 | A kind of silk stocking with buffering sole pressure |
| CN112516828A (en) * | 2020-11-28 | 2021-03-19 | 浙江千禧龙纤特种纤维股份有限公司 | Ultrahigh molecular polyethylene fiber varicose vein socks and production equipment thereof |
Also Published As
| Publication number | Publication date |
|---|---|
| CN107518440B (en) | 2019-01-22 |
| CN109259335A (en) | 2019-01-25 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN104172479B (en) | A kind of antibacterial underwear material | |
| CN103059549B (en) | Antibacterial property resin composite material and preparation method thereof | |
| CN108385374A (en) | A kind of preparation method of silver-loaded silica antiseptic | |
| CN101589853A (en) | Blumea oil microcapsule antibacterial mask and preparation method thereof | |
| CN104650290A (en) | Polymer nano ZnO compound antibacterial agent for synthetic leathers based on in-situ polymerization process and preparation method of polymer nano ZnO compound antibacterial agent | |
| CN104186466B (en) | Long-acting slow release type antibacterial and mouldproof material and preparation method thereof | |
| CN106924803A (en) | A kind of high-performance medical use liquid adhesive bandage and preparation method thereof | |
| CN104927074A (en) | Konjac glucomannan sticking membrane used for sanitary travel sleeping bag and preparation method for konjac glucomannan sticking membrane | |
| CN108914247A (en) | A kind of high antibacterial non-woven fabric and preparation method thereof | |
| CN111364113A (en) | Heat-dissipation slow-release antibacterial artificial grass | |
| CN107594645A (en) | A kind of antibacterial non-slip socks | |
| CN107652518A (en) | A kind of preparation method of novel antibacterial material | |
| CN102010514A (en) | Method and device for preparing nano silver- and porous structure-containing medical high molecular material | |
| CN112962309A (en) | Antiviral slurry special for wall cloth, wall cloth and production method thereof | |
| CN111732410A (en) | A kind of antibacterial ceramic tile containing metal oxide and preparation method thereof | |
| CN107518440B (en) | A kind of antibacterial and non-slip socks that can increase the sock tube | |
| CN104179016B (en) | Antibacterial composite coating for fabric and preparation method thereof | |
| CN111607977B (en) | Antibacterial and antiviral leather and preparation method and application thereof | |
| CN104161044A (en) | Preparation method and application of organic/inorganic compound antibacterial agent | |
| CN106978000A (en) | Far infrared health care inner wall putty powder and preparation method thereof | |
| CN105177807A (en) | Multifunctional deodorant health-care mattress shell fabric and manufacturing method thereof | |
| KR101690523B1 (en) | Producing method for fabric containing functional capsule | |
| CN104450989A (en) | A kind of processing method of sheepskin | |
| CN108912635A (en) | A kind of preparation method of insulating protection gloves | |
| CN109303879A (en) | A kind of traditional Chinese medicine plaster and preparation method thereof for treating eczema |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| PB01 | Publication | ||
| PB01 | Publication | ||
| SE01 | Entry into force of request for substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| TA01 | Transfer of patent application right | ||
| TA01 | Transfer of patent application right |
Effective date of registration: 20181207 Address after: No. 2400 Luqingping Highway, Xujing Town, Qingpu District, Shanghai, 2010 Applicant after: SHANGHAI DONGBEI YAXIN TEXTILE TECHNOLOGY CO.,LTD. Address before: No. 1558, Jiangnan Road, Ningbo hi tech Zone, Zhejiang, Zhejiang Applicant before: NINGBO KEBANG HUACHENG TECHNOLOGY TRANSFER SERVICE CO.,LTD. |
|
| GR01 | Patent grant | ||
| GR01 | Patent grant | ||
| TR01 | Transfer of patent right | ||
| TR01 | Transfer of patent right |
Effective date of registration: 20221028 Address after: 223600 Intelligent Knitting Industrial Park, Shuyang Economic and Technological Development Zone, Suqian City, Jiangsu Province (east of 205 National Road north of Youfu Road) Patentee after: Jiangsu Southwest Intelligent Textile Co.,Ltd. Address before: No. 2400 Luqingping Highway, Xujing Town, Qingpu District, Shanghai, 2010 Patentee before: SHANGHAI DONGBEI YAXIN TEXTILE TECHNOLOGY CO.,LTD. |